NAVIGATING THE POST-TRUTH ERA: TRUST, MISINFORMATION, AND CREDIBILITY ASSESSMENT ON ONLINE SOCIAL MEDIA - Kyza, Eleni A.; Varda, Christiana (AoIR Selected Papers of Internet Research, 2019)
As access to news is increasingly mediated through social media platforms, there are rising concerns for citizens’ ability to evaluate online information and detect potentially misleading items. While many studies have reported on how people assess the credibility of information, there are few reports on processes related to evaluating information online and people’s decision to trust and share the information with others. This paper reports on the first part of a three-phase study which aimed to gain an in-depth understanding of citizens’ practices and needs in assessing the credibility of information shared online and co-create solutions to address this problem. Data were collected from three European countries, through a survey on misinformation perceptions, focus groups, follow-up individual interviews, and co-creation activities with three stakeholder groups. The data were analyzed qualitatively, using, primarily, a grounded theory approach. Results from the citizens’ stakeholder group indicate that personal biases, emotions, time constraints, and lack of supporting technologies impacts the credibility assessment of online news. Study participants also discussed the need for increased media literacy actions, especially in youth. Based on preliminary findings we argue that we need a diversified approach to support citizens’ resilience against the spread of misinformation.